Estudio de factibilidad para la creación de un salón de belleza en la ciudad de Loja. (Período 2022- 2027) - Merino Dávila, Stephanie Michelle (2023)
Nowadays, beauty services have become a necessity for people who, whether for work or personal interest, take care of their image; for this reason, this investigative work is aimed to carry out a "Feasibility study for the establishment of a beauty salon in the city of Loja". (Period 2022-2027), in order to structure a market study that allows identifying supply and demand conditions, prepare a technical-administrative study that determines the operational capacity of the company and finally an economic-financial study that considers, among other things, the investment and financial evaluation. The research method is inductive-deductive and analytical. Additionally, the statistical method was used with the purpose of managing the data collected through direct observation and research instruments such as the interview and survey with questions regarding the frequent use of services in beauty salons, costs, types of services, among others; the same tools were applied to the researched population divided into 399 plaintiffs and 112 bidders. The results obtained were gathered through surveys to the plaintiffs to determine the acceptance of the service in the market. Within the discussion, the market study was carried out where the unsatisfied demand for visits was established 150538, later the marketing strategy is established, determination of the 4 P's of marketing. In the technical study, the installed capacity is detailed, which will be 44% at the beginning, in the same way, the size and location of the company is detailed. The administrative study indicates the organizational model that the company will have, specifying the number of people that will be part of the staff, of providing the different services offered focusing on their work as stipulated in the function’s manual. The financial study indicates the investment needed to implement the project, which is $18360 and will be owned capital. The following indicators are detailed in the financial evaluation: NPV of 20207,38; IRR of 13%; Capital Recovery Period is 4,7. After the analysis of the results, it was possible to determine the viability of the beauty salon, since users require and value good service, quality and convenient prices, all of which allow them to satisfy their needs and create a community with lasting relationships. Keywords: beauty, feasibility study, beauty services, beauty salon, esthetic